PP.04.17: GENETIC AND ENVIRONMENTAL DETERMINANTS OF INAPPROPRIATE LEFT VENTIRCULAR MASS. A TWIN STUDY. (June 2015) - Pucci, G.; Medda, E.; Tarnoki, A.D.; Tarnoki, D.L.; Kovacs, A.; Molnar, A.A.; Battista, F.; Abu Shrkihe, B.; Salemi, M.; Stazi, M.A.; Schillaci, G.
Abstract : Objective: Left ventricular mass (LVM) and its major anthropometric and hemodynamic determinants (body size, blood pressure, stroke volume) are all highly genetically determined. Independently from its absolute value, the amount of LVM that adapts to measures of body size and cardiac workload may be separated from its inappropriate component, namely inappropriate LVM (iLVM), which results from the difference between observed and predicted LVM. An excess of iLVM carries an adverse prognosis in hypertension and in other clinical settings. We evaluated the genetic and environmental components of iLVM in a cohort of monozygotic (MZ) and dizygotic (DZ) twins. Design and method: A cohort of 114 Hungarian and Italian twin pairs (n = 228, mean age 51 ± 13 years, 34% men; Italy = 49 twin pairs, Hungary = 65 twin pairs) underwent M-mode echocardiography for the evaluation of LVM (Devereux formula) and stroke volume (Teichholz method). The inter-individual degree of iLVM was calculated as the ratio between observed-to-predicted LVM, the latter estimated from published equations (de Simone, Hypertension 1998). Intra-class correlation coefficients (ICC) between MZ and DZ and structural equation models were employed to discriminate between the degree of genetic and environmental components of iLVM. Results: Average observed-to-predicted LVM ratio (iLVM) was 1.35 ± 0.36, which did not differ between MZ and DZ couples (1.32 ± 0.34 vs 1.39 ± 0.39, p = 0.20). Age- and sex-adjusted ICC was 0.49 (C.I. 0.28–0.64) in MZ twins and 0.33 (C.I. 0.06–0.54) in DZ twins. Structural equation modelling showed that a considerable proportion of total variance of iLVM is attributable to unique (51%, 95% C.I., 36% to 77%) and shared (18%, 95% C.I., 0% to 54%) environmental factors, while the additive genetic component explained the remaining 31% (95% C.I., 0% to 64%) of the iLVM trait variance. Conclusions: A consistent proportion of total variance of iLVM is explained by acquired environmental factors. Behavioural and therapeutic interventions aiming at reducing the effects of non-hemodynamic factors responsible for the increase of LVM may considerably reduce the burden of iLVM.